Peran Kompetensi Digital, Komunikasi Interpersonal, dan Iklim Organisasi dalam Peningkatan Kinerja Karyawan di PLN UP3 Malang - Lidia Andiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the impact of digital competence, interpersonal communication, and organizational climate on employee performance at PLN UP3 Malang using a quantitative approach. The primary objective is to examine the causal relationship between variables through explanatory methods to empirically test hypotheses. The study population comprised all 89 employees of PLN UP3 Malang. This study attempts to fill a gap in the academic literature, which has rarely integrated these three variables within the context of state-owned energy companies, particularly at PLN UP3 Malang. The results indicate that these three factors contribute significantly to improving employee performance. These findings provide a strategic basis for HR management in designing sustainable human resource development policies. Academically, this study enriches understanding of the factors driving productivity in public organizations. Practically, the results can be applied through intensive digital training, strengthening team communication, and creating a work culture that supports employee innovation and participation. Thus, this study not only contributes to management science but also encourages sustainable organizational transformation at PLN UP3 Malang.